Qubit energy tuner based on single flux quantum circuits - Geng, Xiao; He, Kaiyong; Huang, Rutian; Liu, Jianshe; Chen, Wei (Frontiers in Physics, 2023)
A device called the qubit energy tuner (QET), based on single flux quantum (SFQ) circuits, has been proposed for Z control of superconducting qubits. The QET is created by improving flux digital-to-analog converters (flux DACs) and is capable of setting the energy levels or frequencies of qubits, particularly flux-tunable transmons, and performing gate operations requiring Z control.The circuit structure of the QET is elucidated, consisting of an inductor loop and flux bias units for coarse or fine tuning. The key feature of the QET is analyzed to understand how SFQ pulses change the inductor loop current, which provides external flux for qubits. To verify the functionality of the QET, three simulations were carried out. The first simulation verified the responses of the inductor loop current to SFQ pulses, showing a relative deviation of about 4.259% between analytical solutions of the inductor loop current and the solutions from WRSpice time-domain simulation. The second and third simulations, using QuTip, demonstrated how a Z gate and an iSWAP gate can be performed by the QET, respectively, with corresponding fidelities of 99.99884% and 99.93906% for only one gate operation to specific initial states.These simulations indicate that the SFQ-based QET could act as an efficient component of SFQ-based quantum-classical interfaces for digital Z control of large-scale superconducting quantum computers.